Stability of two self-drilling Orthodontic Temporary Anchorage Devices (TAD) assessed by Histomorphometric Changes - Mohamed, Mahfud; Maher, Amer (Libyan Journal of Dentistry, 2019)
Aims: This work was aimed to evaluate bone density around two types of self-drilling orthodontic miniscrews in mongrel dogs. Materials and methods: two groups of TADs were inserted in the maxillae of six mongrel dogs. Group 1: six tapered self-drilling miniscrews, each of which was inserted in the right buccal side between the roots of the maxillary third premolar (P3). Group 2: Six cylindrical self-drilling miniscrews, each of which was inserted in the right buccal side between the roots of the maxillary first molar (M1 ). All of the TADs were inserted parallel to the occlusal plane. Occlusal radiographic views were taken at different time intervals: pre-insertion, just after insertion (T0), after 4 weeks (T1), after 8 weeks (T2) and after 12 weeks (T3). Using IDRISI Kilimanjaro computer software, the peri-implant area surrounding the apical one third of miniscrew was studied measuring the amount of grey shade. Bone density was measure in five areas (zone1 through zone 5) around the apical 1/3 of the TADs. Paired t- test was used to compare the measurements of the bone density pre-insertion of TADs between roots of M1 and P3, and the bone density post-insertion of TADs in the cylindrical and tapered TAD. The unpaired t-test was used to evaluate the difference in bone density of each zone around the tapered TAD and it correspondent zone around the cylindrical TAD. Results: the significance of the scheduled differences between means of bone density around group1 and group 2 were variable, indicating that the bone density depends on several factors. Conclusion: TAD design has an influence on the bone density. Cylindrical TADs have more bone density around than tapered TADs.